2021
DOI: 10.3389/fpsyg.2021.642689
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Impact of COVID-19 on Student Well-Being and the Mediating Role of the University Support: Evidence From France, Germany, Russia, and the UK

Abstract: The rapid and unplanned change to teaching and learning in the online format brought by COVID-19 has likely impacted many, if not all, aspects of university students' lives worldwide. To contribute to the investigation of this change, this study focuses on the impact of the pandemic on student well-being, which has been found to be as important to student lifelong success as their academic achievement. Student well-being has been linked to their engagement and performance in curricular, co-curricular, and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 66 publications
3
54
1
2
Order By: Relevance
“…Due to strict regulation, the students faced sudden changes in their everyday and academic life. Studies confirmed the negative impact of closure, disruption in academic processes, social distancing, and self-isolation on well-being ( Brooks et al, 2020 ; Wang et al, 2020 ; Kohls et al, 2020 ; Capone et al, 2020 ; Stathopoulou et al, 2020 ; Van de Velde et al 2020 , Burns, Dagnall, Holt, 2020 ; Savage et al., 2020 ; Plakhotnik et al 2021 ; Fekete, 2021 ; Fialho et al, 2021 ; Prasath, Mather, Bhat, & James, 2021 ; Dodd, Dadaczynski, Okan, McCaffery, & Pickles, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 89%
See 1 more Smart Citation
“…Due to strict regulation, the students faced sudden changes in their everyday and academic life. Studies confirmed the negative impact of closure, disruption in academic processes, social distancing, and self-isolation on well-being ( Brooks et al, 2020 ; Wang et al, 2020 ; Kohls et al, 2020 ; Capone et al, 2020 ; Stathopoulou et al, 2020 ; Van de Velde et al 2020 , Burns, Dagnall, Holt, 2020 ; Savage et al., 2020 ; Plakhotnik et al 2021 ; Fekete, 2021 ; Fialho et al, 2021 ; Prasath, Mather, Bhat, & James, 2021 ; Dodd, Dadaczynski, Okan, McCaffery, & Pickles, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 89%
“…A great number of studies described the difficulties students had to encounter due to the pandemic, which had a negative effect on their mental wellbeing ( Brooks et al, 2020 ; Wang et al, 2020 ; Kohls et al, 2020 ; Capone et al, 2020 ; Stathopoulou et al, 2020 ; Van de Velde et al 2020 , Burns, Dagnall, Holt, 2020 ; Savage et al., 2020 ; Plakhotnik et al 2021 ; Fekete, 2021 ; Fialho et al, 2021 ; Prasath, Mather, Bhat, & James, 2021 ; Dodd, Dadaczynski, Okan, McCaffery, & Pickles, 2021 ). Based on the results of these surveys, isolation, difficulties with handling online platforms, anxiety about possible progress with studies, interruption of personal contact with the other students, lecturers and mentors are mentioned as risk factors increasing the number of already existing stress factors related to higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the results are interpreted from Hobfoll’s (1989) conservation of resources theory, which emphasizes that internal resources (such as self-efficacy) at the personal level would allow people to adapt to new, changing, and unfamiliar needs. Before online emergency remote education, the university as an institution could generate external support through either programs or support tutorials that maximized or compensated students’ personal and internal resources that helped to build students’ resilience ( Plakhotnik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to continue online education a few of the universities provided support which was of average quality [ 63 ]. The support by the university was considered as a positive impact of wellbeing [ 64 ]. The current study analyzed university assistance for their students, including any COVID-19-related courses included in their university curriculum, financial and mental help for impoverished students, and online classes.…”
Section: Discussionmentioning
confidence: 99%